Personalised learning environments (part 2): a conceptual model for construction - Syed Khuzzan Alhabshi, Sh Mazlina; Goulding, Jack (Emerald Group Publishing Limited, 2009)

(untitled)
Purpose – The purpose of this paper is to present a conceptual model for a PLE prototype, specifically incorporating learning styles for the UK construction industry.